Ethnic Variability Among Jews is Associated With Hypertension: Results of a Nationwide Study of 1.44 Million Adolescents. (28th November 2019) - Fishman, Boris; Leiba, Adi; Twig, Gilad; Shlomai, Gadi; Orr, Omri; Landau, Regev; Derazne, Estela; Grossman, Ehud
Abstract: BACKGROUND: Adolescent hypertension is a major cardiovascular risk factor that may be related to ethnic variability. Contemporary Jews can be divided into three distinct ethnic groups: Ashkenazi, Oriental, and Sephardi origins. The aim of our study was to investigate the association of ethnicity and hypertension among Israeli adolescents. METHODS: We conducted a population retrospective cohort study of males and females, aged 16–19, eligible for mandatory military service in the Israeli Defense Forces (IDF) between 1994 and 2013. Medical and sociodemographic data, including body mass index (BMI), age, years of education, residential socioeconomic status, and parents' country of birth, were retrieved. Ethnicity of the parents was based upon their country of birth. The examinees were assigned to a certain ethnicity only if both parents had the same ethnicity. Logistic regression models were applied to compute the odds ratio (OR) and 95% confidence intervals (95% CI) for hypertension among the different Jewish ethnicities. RESULTS: The final cohort included 1, 445, 176 adolescents, of whom 716, 289 were born to parents of the same Jewish ethnicity. Ashkenazi ethnicity was associated with an increased risk of hypertension compared to Sephardi and Oriental ethnicities (adjusted OR of 2.93 (95% CI, 2.52–3.41) and 1.56 (1.38–1.77), respectively). Oriental ethnicity was associated with an increased risk of hypertension compared with the Sephardi ethnicity (OR of 1.91 (1.60–2.27)). Similar results were observed in a sub-analysis, which included only Israeli-born examinees. CONCLUSIONS: Our results indicate that ethnicity is significantly associated with hypertension among Jewish adolescents. Ashkenazi Jews had the highest risk of hypertension.